Distribution, climatic relationships, and status of American pikas (Ochotona princeps) in the Great Basin, USA. Issue 1 (1st January 2018) - Millar, Constance I.; Delany, Diane L.; Hersey, Kimberly A.; Jeffress, Mackenzie R.; Smith, Andrew T.; Van Gunst, K. Jane; Westfall, Robert D.
ABSTRACT: To advance understanding of the distribution, climatic relationships, and status of American pikas ( Ochotona princeps ) in the Great Basin, United States, we compiled 2, 387 records of extant pika sites surveyed since 2005, 89 records of documented extirpated sites (resurvey of historic sites), and 774 records of sites with old sign only. Extant sites extended across five degrees latitude and ten degrees longitude, encompassed six subregions, traversed forty mountain ranges, spanned 2, 378 m in elevation (1, 631–4, 009 m), and comprised three of five currently described pika subspecies. A climate envelope for extant sites using the PRISM climate model expands the range of temperature and precipitation values that have been previously described. Extirpated and old-sign sites were mostly found within the geographic and climatic space of extant sites, but often in warmer and drier portions. Considerable overlap of extirpated, old, and extant groups within the same climate space suggests that nonclimatic factors have also contributed to population losses. The broad distribution and enlarged climate envelope of extant pika sites indicate that despite some localized extirpations, pika populations are persisting across Great Basin mountains, and appear to be able to tolerate a broader set of habitat conditions than previously understood.